Microscopic study of the effect of intrinsic degrees of freedom on fusion - Simenel C.; Dasgupta M.; Hinde D. J.; Oberacker V. E.; Umar A. S.; Williams E. (EPJ Web of Conferences, 2015)
Fusion cross-sections are computed for the 40Ca+40Ca system over a wide energy range with two microscopic approaches where the only phenomenological input is the Skyrme energy density functional. The ﬁrst method is based on the coupled-channels formalism, using the bare nucleus-nucleus potential calculated with the frozen Hartree-Fock technique and the deformation parameters of vibrational states computed with the time-dependent Hartree-Fock (TDHF) approach. The second method is based on the density-constrained TDHF method to generate nucleus-nucleus potentials from TDHF evolution. Both approaches incorporate the effect of couplings to internal degrees of freedoms in different ways. The predictions are in relatively good agreement with experimental data.